Acupuncture for postoperative gastroparesis syndrome: A protocol for systematic review and meta-analysis. Issue 51 (23rd December 2022) - Li, Wei; Zhang, Ning; Xiao, Mengmeng; Liu, Li; Yao, Lan
Abstract : Background: Postsurgical gastroparesis syndrome (PGS) is an early common complication after upper abdominal surgery, especially which occurs mainly after gastroduodenal operation. Acupuncture, a complementary and alternative therapy, has been widely used in China because of its significant effect and few side effects. We conduct a protocol for systematic review and meta-analysis to assess the efficacy and safety of acupuncture for the treatment of PGS. Methods: This systematic review was registered in the PROSPERO network (registration number: CRD42022369167). We will follow the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocol to accomplish the study. Following databases will be searched: PubMed, MEDLINE, EMBASE, Cochrane Library, China National Knowledge Infrastructure, Wanfang data, Chinese Scientific Journals Database, and China biomedical literature database. All randomized controlled trials (RCTs) on the application of acupuncture in the treatment of patients with PGS will be included. The risk of bias of the included studies will be assessed using the Cochrane tool of risk of bias. All statistical analyses will be conducted using the STATA13.0 software. Results: This study is ongoing and the results will be submitted to a peer-reviewed journal for publication. Conclusion: The conclusion of this review will provide evidence to judge whether acupuncture is an effective intervention for patient with PGS.